EFL Students’ Challenges In Learning Speaking Skills During Online-to-Offline Transition Era - Fajaryani, Nunung; Herliza, Gita; M. Ali. , Rd. (Universitas Cokroaminoto Palopo, 2023)
This research aimed to explore the challenges faced by EFL students’ in learning speaking skills during the online-to-offline transition era, then the difference between the experience of learning speaking skills during online and offline, and also explain the potential solutions that EFL students’ do to overcome the challenges. The site of this research was an English study program at one public university in Jambi. The participants in this study were five fourth-semester students consisting of 3 different classes who have completed speaking lessons in 1-3 semesters. This research employed qualitative study. In collecting the data, the researcher used interviews as a primary instrument. The results of this research indicated that there were two themes of challenges faced by EFL students in speaking English, including lack of vocabulary (academic word issues), and nervousness (communication apprehension). This research also revealed that there were four themes of differences in online and offline learning, including learning process (inattentiveness unmotivated, attentiveness and motivated), classroom activities (non-interactive and interactive learning), time management (undisciplined and disciplined learning), and learning outcomes (understanding the material). Last but not least, this research also pointed out that the participants used three strategies or potential solutions to overcome their challenges. Those strategies are metacognitive strategies (preparing vocabulary), cognitive strategies (entertainment platform), and social strategies (asking and practice). Finally, the transition era gives new experiences to students. They do not experience challenges in terms of environment and internet issue as they face during online learning.